Two stage integrated on-board charger for EVs - Vankayalapati B.T.; Singh R.; Bussa V.K. (My University, 2025)
On-Board integrated battery chargers integrate the charger into the powertrain of an electric vehicle (EV). This reduces the overall cost of an EV by eliminating the need for a seperate charger. In this paper a two stage integrated on-board battery charger for EVs is proposed. In the proposed charger topology, the 3-phase traction inverter in the vehicle powertrain is reconfigured as a front end AC-DC boost rectifier power factor correction (PFC) stage cascaded by a DC-DC converter stage during charging operation to charge the battery. During motoring operation, it works as a single stage DC-AC 3 phase inverter. Due to the presence of a DC-DC stage during charging, the proposed integrated charger topology is applicable to a wide range of EVs with different battery pack voltage ratings. It is particularly suitable for EVs with low battery pack voltage. Also, the proposed two stage topology offers wide possibilities in terms of the control strategy employed. The proposed concept is validated with experimental results of a 400 W prototype. The performance of the proposed charger in charging mode is also validated with CC-CV charging of a 24 V-30 Ah lead acid battery. © 2018 IEEE.